The The Influence of Nutritional Action on Mother's Knowledge About Feeding And The Level of Energy, Zink and Vitamin C Consumption of Wasting Toddlers in Purwodadi Village, Malang City - Reny Seftiani; Komalyna, I Nengah Tanu; Riyadi, Bastianus Doddy (Media Gizi Kesmas, 2025)
Background: Indonesia still faces quite serious nutritional problems, especially in children, because the first five years of a child's life are very vulnerable to nutritional problems. Therefore, balanced nutritional needs for toddlers must be met properly. Nutritional problems that arise are always related to food intake factors in children. If balanced nutritional needs in toddlers are not met properly, they can experience nutritional disorders such as malnutrition. Objectives: To analyze the effect of nutritional assistance on the knowledge of mothers of toddlers, the level of energy consumption, zinc, and vitamin C of wasting toddlers. Methods: This study is a quasi-experimental study targeting toddlers aged 12 to 59 months. Respondents were taken using the non-probability sampling method, namely total sampling. The data collected included the knowledge of mothers of toddlers taken with a questionnaire, the level of energy consumption, zinc, and vitamin C obtained by filling out the 24-Hour Food Recall form. The study was conducted by providing intervention in the form of nutritional assistance three times within three weeks. Data analysis tests used the paired t test, Wilcoxon signed rank, independent t-test, Mann Whitney U test. Results: Nutritional assistance on the knowledge of mothers of toddlers before and after in the treatment group (p=0.003) had a more significant effect than in the control group (p=0.011). Then the level of consumption before and after in the treatment group also had a significant effect, namely energy (p<0.001), zinc (p=0.006), and vitamin C (p=0.004). However, the level of consumption before and after in the control group did not have a significant effect, namely energy (p=0.583), zinc (p=0.366), and vitamin C (p=0.534). Conclusion: Nutritional assistance can affect the knowledge of mothers of toddlers, consumption of energy, zinc, and vitamin C of toddlers before and after the intervention in the treatment group. Meanwhile, in the control group it only affected the knowledge of mothers of toddlers.